PENGARUH MUSIUM TARUNA ADBUL DJALIL AKADEMI MILITER TERHADAP WAWASAN KEBANGSAAN PELAJAR SMA KOTA MAGELANG - Agus Djoko Purnomo; Tjatur Supriyono; Eko Ariyanto; Afrian Satria Nugraha (PPM Sdirjianbang Akademi Militer, 2024)
A sense of Nationalism and National Insight is related to curiosity about the history of the Nation. Museums are a medium and means to assist knowledge of history because they play a role in the development of National culture, especially National education and Nationalist motivation. The Abdul Djalil Cadet Museum is a museum located at the Magelang City Military Academy. The Abdul Djalil Cadet Museum is one of the educational facilities at the Military Academy which visually presents a collection that plays a large role in the education process for future leadership officers. This research aims to find out how much influence the Abdul Djalil Military Academy Cadet Museum has on the National Insight of Magelang City High School Students and the most dominant factors influencing the Abdul Djalil Cadet Museum on the National Insight of Magelang City High School Students. The research uses quantitative methods with the technique used using Randon Sampling, using the Slovin formula. The population of this study was the average number of high school students who visited the Abdul Djalil museum within a period of 4 months with a sample of 60 high school students in Magelang City. The research instrument uses a questionnaire. Data were analyzed using SPPS version 11.5 and the results of the analysis were presented in table form. The results of Taruna Abdul Djalil's museum research on the National Insight of Magelang City High School students had a very strong influence of 0.804 and simultaneously or jointly it was 0.647 and the remainder was 0.353. The most dominant factor in the selected Museum variable is the story indicator with a percentage of 58.3 so it can be concluded that the story factor contained in the Adbul Djalil Taruna Museum variable greatly influences museum visitors towards national insight.